Penggunaan Teknologi Informasi dan Komunikasi dan Implikasinya terhadap Ketangguhan Mata Pencaharian Nelayan - ASIRIN ASIRIN; TETI A. ARGO (P4W LPPM IPB, 2017)
The livelihood of fishermen that importantly contributes to regional and rural development in coastal areas has been influenced by climate change and other pressures. On the other hand, the development of Information and Communication Technology (ICT) can be used by fishermen to develop their livelihood resilience. This research aims to explore the use of ICT and its implication to the livelihood resilience of fishermen. This research used qualitative research design using case study in Eretan Wetan Village, Indramayu Regency. The primary data was collected through interview, situational observation, activity observation, and physical artifact observation. Secondary data was also collected as supporting data to describe research context. The analysis was done using open coding to identify themes and to develop the description of those themes. The research found that fishermen that are used to ICT can improve their access to information, enhancing knowledge, enhancing and maintaining network and cooperation, and facilitating participation in the community, and eventually experiencing learning process. By experiencing learning process, fishermen will have the capability to identify information and knowledge, capability to understand challenge and opportunity, and capability to transfer and share knowledge using ICT. Therefore, fishermen will then have the capability to diversifies operational location of fishing and source of information and knowledge which are useful to redevelop access, assets, and self organization capability. These process will be cyclic and accumulate to strengthening their livelihood resilience.